Odpowiedzi

2010-02-03T18:48:12+01:00
6x-24-2=6x-26
2x+2-3x+3=-x+5
-3y+6+4y+4=y+10
5x-5y-5-4y-8=-9y-13+5x
6a+2b-2a+2b=4b+4a
2x-2-2x+-2

-2a+4b
3x-y+1-x-y+y-x=x+1-y
-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
2ab+a+3-3ab+a-3=-ab+2a
4x²-3x-x-0,1x²-x²+0,1x=-3.9x+4x²-0,1x²-x²
1 5 1
2010-02-03T18:59:18+01:00
30.
a.6(x-4)-2=6x-24-2=6x-26
b.2(x+1)-3(x-1)=2x+2-3x-3=x-1
c.-3(y-2)+4(y+2)=-3y+6+4y+ 8=y+14
d.5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e.2(3a+b)-2(a-b)=6a+2b-2a-2b=4a
f.1/2(4x-4)-2x=2x-2-2x=-2

25.
a. ...=a+b-2a+b-a+2b=-2a-2b
b. ...=3x-y+1-x+y+y-x=x-y+1
c. ...=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
d. ...=2ab+a+3-2ab+a-3=-ab
e. ...4x(kwadrat)-3x-x-0,1x(kwadrat)-x(kwadrat)+0,1x=
=2,9x(kwadrat)-3,9x

1 5 1
Najlepsza Odpowiedź!
2010-02-03T19:02:22+01:00
Myślę że jest dobrze
zadanie30
a) 6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2+3x=5x-1
c) -3(y-2)+4(y+2)=-3+6+4y+6=1y+12
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=1x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f) 1/2(4x-4)-2x=2x-2-2x=-2

Zadanie25
a)(a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=-2a+4b
b) (3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x+y+1
c)-(kx+ny)-(3kx+2ny)+5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=1kx
d)(2ab+a+3)-(3ab-a+3)=2ab+a+3-3ab+a-3=-1ab+2a
e) (4x2( ta 2 na końcu to ma być że do kwadratu)-3x)-(x+0.1x2(znowu do kwadratu))-(x kwadrat - 0.1x)= 4x kwadrat - 3x-x-0.1x kwadrat-x kwadrat +0.1x=2,9x kwadrat-2,9

POZDRAWIAM
1 5 1